2005
DOI: 10.1111/j.1467-9396.2005.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Mercantilism, Oligopoly, and Trade*

Abstract: The authors propose a new model of trade between developing and advanced economies to capture the effects of important asymmetries in the organizations of their industries. This model demonstrates how the industrial structure of a developing economy can evolve to produce what the authors call "implicit mercantilism." Free entry plus domestic oligopoly in a developing economy, when combined with competitive behavior in developed countries, generates several distinct stages of mercantilism hitherto unrecognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Hence, slope of the residual demand, that is, AP AðQ−BÞ ¼ f V f −1 ðA−PÞ , remains the same for a given price.20 We are deeply grateful to Hiroshi Ohta for this insight. SeeMcGuire and Ohta (2005) for a proof of this type applied in a different context.…”
mentioning
confidence: 93%
“…Hence, slope of the residual demand, that is, AP AðQ−BÞ ¼ f V f −1 ðA−PÞ , remains the same for a given price.20 We are deeply grateful to Hiroshi Ohta for this insight. SeeMcGuire and Ohta (2005) for a proof of this type applied in a different context.…”
mentioning
confidence: 93%
“…Similar recommendations had already been developed by Jean Bodin (1576) in his Les six livres de la république 1576. He pledged a trade surplus by means of export duties on goods whose importation is indispensable to foreign countries, low import duties on required raw materials, and high import tariffs on foreign finished products (Kolb, 2017;Tilly, 2015;McGuire & Ohta, 2005).…”
Section: Mercantilismmentioning
confidence: 99%
“…Note that excessive firm entry is defined in a similar manner to excessive capacity, in which the equilibrium unit cost exceeds the minimum average cost McGuire and Ohta (2005). andOhta and McGuire (2015) showed that excessive entry can occur in an oligopolistic market for a developing economy.…”
mentioning
confidence: 99%